2001
DOI: 10.1097/00003246-200103000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a dual inhibitor of tumor necrosis factor-α and interleukin-1 on lipopolysaccharide-induced lung injury in rats: Involvement of the p38 mitogen-activated protein kinase pathway

Abstract: FR167653 administration decreased serum TNF-alpha and IL-1beta concentrations, which was associated with decreased lung injury and lethality. The mechanism responsible for the decreased TNF-alpha and IL-1 may be related to the inhibitory effect of FR167653 on p38 MAP kinase activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…The samples were dried in a hot air oven at 80°C for 72 h. Later, the dried tissue was weighed. The wet-to-dry ratio was calculated with the following equation: ratio = wet weight/dry weight (Yoshinari, 2001). …”
Section: Determination Of Pulmonary Edemamentioning
confidence: 99%
“…The samples were dried in a hot air oven at 80°C for 72 h. Later, the dried tissue was weighed. The wet-to-dry ratio was calculated with the following equation: ratio = wet weight/dry weight (Yoshinari, 2001). …”
Section: Determination Of Pulmonary Edemamentioning
confidence: 99%
“…On the other hand, FR167653 was first discovered as a potent inhibitor of tumor necrosis factor (TNF)-␣ and interleukin-1␤ production (Yamamoto et al, 1996(Yamamoto et al, , 1997. Recent reports have shown that FR167653 inhibits the activation of p38 MAPK by suppressing the phosphorylation of p38, preferentially in the ␣ isoform, but not in the ␥ isoform Takahashi et al, 2001;Yoshinari et al, 2001). We therefore investigated whether not only SB203580 but also FR167653 blocks the SNL-induced thermal hyperalgesia (Fig.…”
Section: Inhibition Of P38 Activation Attenuates L5 Snl-induced Thermmentioning
confidence: 99%
“…4 Activation of p38 MAPK can induce the production and secretion of proinflammatory cytokines such as interleukin-1␤ and tumor necrosis factor-␣ (TNF-␣). 5 In turn, interleukin-1␤ and TNF-␣ can activate p38 MAPK, which leads to autocrine and paracrine promotion of an inflammatory response that exacerbates kidney injury. 6,7 Increased activity of p38 MAPK has been observed in patients suffering from inflammatory bowel disease, human diabetic nephropathy, and glomerulonephritis.…”
mentioning
confidence: 99%